ANALISIS BEA PEROLEHAN HAK ATAS TANAH (PERBANDINGAN BERDASARKAN NJOP DAN PETA ZNT) DI KECAMATAN TOMOHON TENGAH KOTA TOMOHON (Analysis of Charges on Land Right Acquisition (Comparative Based on Property Tax Selling Value and Land Value Zone Map) in Central Tomohon District, Tomohon City) - Fidrian Sumardianto; Melsje Yellie Memah; Grace A. J. Rumagit (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2022)
This study aims to analyze the comparison of the revenue from Land and Building Title Transfer Duty (BPHTB) based on the Property Tax Selling Value of Tax Object (NJOP PBB) with the Land Value Zone (ZNT) Map and to analyze the percentage of potential increase in BPHTB revenue based on the Land Value Zone Map in Central Tomohon District, Tomohon City. This research was carried out in Central Tomohon District, Tomohon City, North Sulawesi Province, which was carried out for 2 (two) months, starting from March to April 2020. The data used in this study were secondary data in the form of data on local revenue from the property tax in 2018. In addition, the data collected were the 2018 Tomohon City ZNT map; List of Tax Assessment Associations (DHKP) in Central Tomohon District in 2019; Administrative Map of Central Tomohon District; and Fees for Acquisition of Land and Building Rights in 2019. The method used in this research was descriptive quantitative method and analyzed and described using statistical methods. Determination of the sample in this study was carried out using the saturated sampling method. The population in this study were all tax objects imposed by BPHTB inCentral Tomohon District, Tomohon City, a total of 74 areas of tax objects. The results showed that there was a significant difference between BPHTB receipts based on the NJOP and BPHTB revenues based on the ZNT map in Central Tomohon District, Tomohon City, where from the test results, the BPHTB acceptance value based on the ZNT map map was greater than the BPHTB revenue value based on the NJOP. With these results, it is suggested to the Tomohon City Government to immediately optimize the use of the ZNT map as an instrument in determining market value in order to increase the potential for BPHTB revenue in Tomohon City.